Land Trusts in Florida: A Brief Guide to Land Trusts for Protecting Land in your Community - Benjamin North; Elizabeth Frances Pienaar (EDIS, 2017)
A land trust is a private nonprofit organization that owns and manages land to protect its natural, economic, and cultural value.  This document provides an overview of the role that land trusts plan in conservation, and how landowners may contact or create a land trust.